1997
DOI: 10.1002/(sici)1097-0215(19970422)74:2<189::aid-ijc9>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-transporter-type-I-gene amplification correlates with Sialyl-Lewis-X synthesis and proliferation in lung cancer

Abstract: Increased glucose transport is a common characteristic of most tumors. To examine the role of elevated glucose uptake in lung cancer, we performed PCR amplification of 2 facilitative glucose transporter genes (GLUT1 and GLUT3) and immunohistochemical staining for GLUT1, proliferating cell nuclear antigen (PCNA), and sialyl Lewis 3 (sLe x ) on tumor specimens from 327 patients with lung cancer who underwent surgical resection from 1980 to 1993. To evaluate the relationship between GLUT, a-2,3-sialyltransferase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 19 publications
2
33
0
1
Order By: Relevance
“…This result is supported also by a recent finding that disruption of the gene for a major galactosyltransferase results in a remarkable reduction of selectin-ligand expression in mice (47). Although the exact mechanism of the relationship between GLUT1 induction and sialyl Lewis x͞a is not clear, the good correlation of GLUT1 expression and sialyl Lewis x expression in clinical samples is known (12). Interestingly, GLUT1 encodes the major cellular transporter for not only glucose but also galactose.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…This result is supported also by a recent finding that disruption of the gene for a major galactosyltransferase results in a remarkable reduction of selectin-ligand expression in mice (47). Although the exact mechanism of the relationship between GLUT1 induction and sialyl Lewis x͞a is not clear, the good correlation of GLUT1 expression and sialyl Lewis x expression in clinical samples is known (12). Interestingly, GLUT1 encodes the major cellular transporter for not only glucose but also galactose.…”
Section: Discussionmentioning
confidence: 52%
“…Increased expression of UDP-galactose transporter gene (UGT1) in cancers was also suggested to be involved in the induction of these selectin ligands, because the introduction of the gene for UDP-galactose transporter conferred the induction of sialyl Lewis a and sialyl Lewis x expression on cultured cancer cells (8). Other investigators have suggested a role for fucosyltransferase VII (9)(10)(11) and even the involvement of another sugar transporter, GLUT1, for induction of sialyl Lewis x in cancers (12). However, the exact mechanism underlying this transcriptional induction has remained uncharacterized.…”
mentioning
confidence: 99%
“…GLUT1 expression in tumors also correlates with the survival of patients. In lung, colorectal, ovarian, laryngeal, and breast carcinomas, high levels of GLUT1 or GLUT3 in the tumors were significant indicators of decreased survival (Baer et al, 1997;Ogawa et al, 1997;Younes et al, 1997;Haber et al, 1998;Cantuaria et al, 2001;Kang et al, 2002). GLUT1 staining has also been identified in 25% of hyperplastic breast tissue and 25% of histologically normal breast tissue adjacent to tumors (Alo et al, 2001).…”
Section: Glut Expression In Tumorsmentioning
confidence: 99%
“…Upregulation of fucosyltransferase activity and subsequent fucosylation of carbohydrate precursors is correlated with tumour progression and poor prognosis (Holmes, 1990;Sun et al, 1995;Ogawa et al, 1996). Furthermore, experimental modulation of a(1,2)fucosyltransferase activity can change the metastasizing properties of tumour cells (Labarriere et al, 1994;Goupille et al, 1997).…”
Section: Discussionmentioning
confidence: 99%